the Teacher’s Perception to the Impact of Playing Gadget for Early Childhood’s Mental Health - Desni Yuniarni (STKIP Singkawang, 2019)
Playing games using gadgets in early childhood is now a common thing. Children mostly spend their time playing gadgets alone rather than playing with their friends. This has an impact on their mental development, especially their social and emotional development. Unfortunately, it has not become a concern for the parents. They assume that playing gadget would not affect their children’s mental development at all. Therefore, this study aims to find out how is the teacher's perception of playing gadgets for early childhood mental health, especially in their social and emotional aspects. This was a qualitative study, in the form of a case study. Data were obtained through interviews and focused group discussions by 7 kindergarten teachers from 4 different classes. The study result reveals that all the teachers had the same perceptive that gadget has both positive and negative effects on early childhood's mental health. The positive impact of the gadget for early childhood's mental health is the contains of the games can stimulate the creativity and imagination for the children. Besides, the games in the gadget should be educative so they can learn in a fun way. The positive emotion of children when learning using gadgets will also maintain their mental health. The negative impact of the gadget for early childhood's mental health is if there they become addicted to the gadget so they spend more time playing gadget and refuse to interact with other people. As an effect, they will face difficulty in communicate with other people, get angry easily, hard to concentrate, unruly, which such things may cause deterioration in their mental health. Finally, teachers and parents as a significant person for the children must control the children while playing gadgets and give the rules and boundaries for the children to maintain their children's mental health.